Costa Rica - Cortés Ramos, Alberto (2014)
Costa Rica constitutes a significant exception to Central America’s pattern of unequal development and authoritarian political regimes. Since the 1948 civil war, the country has experienced six decades without violent conflicts and has benefited from growing levels of human development and a relatively vibrant democracy (Lehoucq 2010). Costa Rica’s exceptionalism was particularly evident during the period 1950–80. The country expanded the social insurance system founded in 1940 and secured broad access to health, education, potable water, electricity, insurance and many other services. During these three decades, Costa Rica also developed a more equitable economic model than most other developing countries. An emerging elite gathered around the left-of-centre Partido de Liberación Nacional (PLN—National Liberation Party), expanded the role of the state as employer and producer, and created a system of incentives for new producers. In doing so, they aimed to expand their own economic opportunities, but also contributed to the significant growth of small and medium-sized enterprises and co-operatives (Martínez Franzoni and Sánchez- Ancochea 2013a; Rovira 2000). By 1980 Costa Rica had a lower level of land and income inequality than neighbouring countries and was regarded as one of the few examples in the developing world of a social democracy with universal social policies (Filgueira 2007; Sandbrook et al. 2007).